New insights into the Upper Palaeolithic of the Caucasus through the study of personal ornaments. Teeth and bones pendants from Satsurblia and Dzudzuana caves (Imereti, Georgia). - José-Miguel Tejero; Guy Bar-Oz; Ofer Bar-Yosef; Tengiz Meshveliani; Nino Jakeli; Zinovi Matskevich; Ron Pinhasi; Anna Belfer-Cohen (PLoS ONE, 2021)
The region of western Georgia (Imereti) in the Southern Caucasus has been a major geographic corridor for human migrations during the Middle and Upper Paleolithic. Data of recent research and excavations in this region display its importance as a possible route for the dispersal of anatomically modern humans (AMH) into northern Eurasia. Nevertheless, within the local research context, bone-working and personal ornaments have yet contributed but little to the Upper Palaeolithic (UP) regional sequence's characterization. Here we present an archaeozoological, technological and use-wear study of pendants from two local UP assemblages, originating in the Dzudzuana Cave and Satsurblia Cave. The ornaments were made mostly of perforated teeth, though some specimens were made on bone. Both the manufacturing marks made during preparation and use-wear traces indicate that they were personal ornaments, used as pendants or attached to garments. Detailed comparison between ornament assemblages from northern and southern Caucasus reveal that they are quite similar, supporting the observation of cultural bonds between the two regions, demonstrated previously through lithic techno-typological affinities. Furthermore, our study highlights the importance attributed to red deer (Cervus elaphus) by the UP societies of the Caucasus in sharing aesthetic values and/or a symbolic sphere.